Analisis Pengaruh Exit Toll Terhadap Tata Guna Lahan di Kabupaten Brebes - Mukhlis, Jafar; Soetomo, Sugiono (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2017)
Brebes district is one of areas that got impact of development â€œTrans Jawaâ€ highway route. Network route is often becomeÂ  a trigger of changing the land use arrangement. However, base on common knowledge, the highway network route will bring up new region and kill the old region. The development of the new region has started in the knot area of the exit highway, the region is dominated with restaurants and Brebes Districâ€™s souvenir shops. The main purpose of this research is understanding the influence of exit highway on the land use in Brebes District. The researchâ€™s data has been analized by one of qualitative method, analysis descriptive qualitative technique. The conclusion of the reseach is the three knot areas of exit highway have their own characteristic. The Pejagan and East Brebes have their impact on land use around the knot corridor. However,Â  the West Brebesâ€™s impact is the changing of utilization around the corridor and it didnâ€™t impact the land use around it. The changing has its own impact to the space structure in Brebes District as there is new regionâ€™s development in the knot of exit highway. On the opposite, this new development has its own negative impact on the old corridor that has developed before, especially to the north route. The business around north corridor experienced the degression of the sales as the outcome of the road userâ€™s new route (Trans Jawa highway route), just like Bulakamba and Diponegoro Corridors.